Media Pembelajaran Interaktif Berbasis Mentimeter untuk Pembelajaran Teori Musik Anak Berkebutuhan Khusus: (Studi Kasus: SLB Negeri Surakarta) - Rr. Diana Insyafari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
Technology in education continues to evolve, offering new opportunities for more interactive teaching and learning, especially for children with special needs. One innovation that can be utilized is Mentimeter, an interactive tool that allows teachers and students to engage in a dynamic learning environment. This article discusses the implementation of Mentimeter as an interactive learning medium in teaching music theory to children with special needs. The objective of this research is to examine the effectiveness of Mentimeter in enhancing students' understanding and engagement with music theory material. Using the classroom action research method, this study involved 20 students from SLB Negeri Surakarta with various special needs who participated in music lessons over a period of three months. The results of the research indicate that the use of Mentimeter increased students' active participation and facilitated a better understanding of the material.